Three-Dimensional Full-Field Strain Measurements across a Whole Porcine Aorta Subjected to Tensile Loading Using Optical Coherence Tomography–Digital Volume Correlation - Acosta Santamaría, Víctor A.; Flechas García, María; Molimard, Jérôme; Avril, Stephane (Frontiers in Mechanical Engineering, 2018)
Optical Coherence Tomography (OCT) combined with Digital Volume Correlation (DVC) is a suitable technique to investigate the biomechanical behavior of biological tissues at the microscale. However, to characterize the whole thickness of large human or porcine arteries, the use of osmotic tissue clearing agents, such as propylene glycol, is unavoidable due to intrinsic tissue scattering of light. The mechanical response of biological tissues immersed in tissue clearing agents has been poorly investigated so far. Nevertheless, understanding the mechanisms of tissue clearing could be helpful for developing safe optical-clearing methods for possible in vivo applications. The goal of the present work is to combine OCT and DVC to measure displacement and strain fields in porcine aortic tissues immersed in polypropylene glycol and subjected to stress-relaxation uniaxial tension. Displacement and strain fields are measured across the whole thickness of the porcine aortic wall for the first time. Measurement uncertainties and optimal OCT-DVC parameters are determined to define useful technical recommendations for future similar analyses. It is known that the main effect of polypropylene glycol is a significant increase of collagen fibril packing density due to important loss of water (dehydratation). It results in a pronounced stiffening of the aortic tensile response when compared to the response of the same tissue immersed in PBS. This effect is reversible when the aortic tissue is removed from polypropylene glycol and immersed again in PBS. Another effect is a dramatic reduction of the Poisson’s effect during tensile loading. But the OCT-DVC measured strain fields also reveal heterogeneities of this effect among the different layers of the aorta. It appears that the reduced Poisson’s effect is concentrated in the media layer, whereas the adventitia and intima layer keep a usual Poisson’s effect of nearly incompressible tissues. It is concluded that further work should be conducted on how the smooth muscle cells highly present in the media layer are affected by polypropylene glycol immersion for a better understanding of these effects.